PENGARUH SHOT PEENING TERHADAP KARAKTERISTIK PERMUKAAN SS 301 SETELAH PROSES ANIL - Ratna Kartikasari; Wartono; Muhammad Oky Sadewa (Fakultas Teknik - Universitas Riau, 2022)
SS 301 is an austenitic stainless steel which has ductile properties, very high corrosion resistance and non-hardenable. The development of the SS 301 application demands a good combination of corrosion resistance and surface hardness properties. Efforts are needed to increase the surface hardness of the SS 301 by cold working. This research aims to study the effect of shot peening on the surface characteristics of SS 301 after annealing process. The annealing process was carried out at temperatures of 800 ° C, 900 ° C and 1000 ° C. The shot peening process is carried out using alumina particles with a size of 0.8-1 mm for 20 minutes with a pressure of 6-8 bar. The tests carried out are chemical composition, microstructure, hardness and corrosion resistance. The chemical composition result showed that SS 301 contained Cr 18.32%, Ni 7.84%, Mn 1.5% and C 0.31%. The microstructure of SS 301 consists of austenite structure with a semi- dendritic pattern. The annealing and hardening process changed the structure of the austenite into equiaxed and the shot peening resulted in fine austenite grains on the surface. In general, the shot peening process increased hardness but decreased SS 301 corrosion resistance.